Analysis of distortion, corrosion and mechanical properties of welded CSN Civil-300 steel U-type profiles - Pereira, Josemairon Prado [UNESP]; Hernandez, Bruno Agostinho [UNESP]; de Magalhães Bento Gonçalves, Gilberto [UNESP]; Sousa, Edson Antonio Capello [UNESP] (Springer Nature, 2024)
Several factors affect the performance, manufacturing and assembly of metallic profiles: equipment, welding parameters and consumables. CSN Civil-300 steel profiles are widely used to obtain high-quality welded joints. Three factors in the welded joints need to remain nearly invariable and within predictable limits: distortion, corrosion and mechanical properties. However, industries still have problems with welding steel profiles, such as warping misalignment, misfit and poor mechanical properties. As a result, it is necessary to have a calibrated and affordable methodology for welding CSN Civil-300 steel profiles on the factory floor. Therefore, this study aims to analyse the mechanical performance of CSN Civil-300 steel profile–welded joints using a robot welding machine. A GMAW (metal active gas) welding process was applied to a CSN Civil-300 type U 100 × 50 profile, 3.0-mm thick, employing a Motoman UP6 robotic arm in butt joints, with and without dots. Two different rod electrode types were used (AWS ER70S-3 and ER70S-6), with a 75%Ar/25%CO2 shielding gas and current density welding set at 160.6 A and 20.5 V. A three-dimensional scanning methodology was adopted to investigate welded joint distortions. While salt spray accelerated, corrosion test was used to analyse deterioration. The mechanical properties were analysed by macrography, microhardness and chemical analyses in the heat-affected zone (HAZ). It was found a distortion displacement was lower than 450 μm on the sample’s surface, and a mass loss of 10.1 μm/year was detected in terms of corrosion resistance. There was also evidence of chemical heterogeneity between the base metal and weld, mainly in the manganese content with an average reduction of 13% in microhardness measurements when AWS ER70S-3 electrode was used. By using calibrated welding parameters and a welding robot, it was possible to obtain mechanically resistant high-quality standardised welds. This procedure can be further improved by using other profile types to implement new robotic welding procedures.
Keywords: Corrosion; Distortion; Mechanical properties; Metallic structures; Welded joint